Pengaruh Pajak Hiburan, Pajak Hotel, dan Pajak Restoran terhadap Pendapatan Asli Daerah - Harrie Yudha Pahlawan; Diana Airawaty (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to analyze the effect of entertainment tax, hotel tax, and restaurant tax on Regional Original Revenue (PAD) in the Special Region of Yogyakarta Province during 2020-2024. This research is motivated by the urgency of optimizing regional tax revenues to support regional financial independence, particularly in regions with significant tourism potential such as Yogyakarta. The research method used is a quantitative approach employing secondary data in the form of time series data obtained from the DIY Tourism Statistics Book and official regional government documents. Data analysis techniques were conducted through descriptive statistical analysis, classical assumption tests including normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression analysis using IBM SPSS Statistics version 24. The results showed that entertainment tax has a positive and significant effect on PAD with a t-value of 33.012 and a significance value of 0.033. Hotel and restaurant taxes also have a positive and significant effect on PAD with a t-value of 5.386 and a significance value of 0.000. Simultaneously, entertainment tax as well as hotel and restaurant taxes significantly affect PAD with an F-value of 14783.841 and a significance value of 0.000. These findings show that optimizing entertainment, hotel, and restaurant tax revenues can serve as strategy for local governments to strengthen fiscal independence and support sustainable regional development financing.